MacEwan University Library’s pedagogical shift: using active learning activities during first-year information literacy sessions - Shamchuk, Lisa; Plouffe, Leah (My University, 2013)
Arising from K–12 education, the pedagogical concept of active learning is becoming more and more commonplace in face-to-face library Information Literacy (IL) sessions. MacEwan University Library decided to update IL sessions to incorporate active learning activities, a decision which not only benefited the engagement of students and faculty, but the librarians as well.
Keywords: active learning; information literacy